Journey of a Reformed scholar and emerging Pentecostal: Missional living in light of diversity - White, Peter (Verbum et ecclesia, 2025)
This article explores the transformative journey of the author, a Pentecostal theologian, within the Reformed academic environment of the University of Pretoria. Central to this narrative is the mentorship and hospitality of Prof. Nelus Niemandt, who was then the Moderator of the Dutch Reformed Church. Despite our differing theological backgrounds, Prof. Niemandt exemplified ecumenical leadership by hosting me during my PhD studies, fostering an environment of mutual respect, humility and learning. This relationship highlights the practical application of missional living amid cultural, racial and theological diversity. Through personal reflections, this article delves into the profound impact of Prof. Niemandt’s mentorship on the author’s academic and personal life, illustrating a model of inclusive and transformative scholarship. Intradisciplinary and/or interdisciplinary implications: The article is underpinned by the missiological concept of ‘Life in its fullness’. The World Council of Churches affirms that ‘life in all its fullness is Jesus Christ’s ultimate concern and mission’.